`a^3+b^3-6ab=-11<=>(a+b)^3-3ab(a+b)-6ab=-11<=>(a+b)^3-3ab(a+b+2)=-11`
Đặt `{(S=a+b),(P=ab):}`
Khi đó ta có `S^3-3P(S+2)=-11<=>(4(S^3+11))/(3(S+2))=4P`
Lại có `S^2>=4P` nên `S^2>=(4(S^3+11))/(3(S+2))`
`<=>(S^3-6S^2+44)/(3(S+2))<=0(S\ne-2)`
- TH1:
`{(S^3-6S^2+44<=0),(3(S+2)>0):}<=>`$\begin{cases} S\leq-2,30213805\\S> -2\end{cases}$`<=>-2<S<-2,30213805(` Vô lý `)`
- TH2:
`{(S^3-6S^2+44>=0),(3(S+2)<0):}<=>`$\begin{cases} S\geq-2,30213805\\S< -2\end{cases}$`<=>-2,30213805<S<-2`
mà `-7/3=-2,33333...<-2,30213805` nên `-7/3<S<-2(đfcm)`
`a^3+b^3-6ab=-11<=>(a+b)^3-3ab(a+b)-6ab=-11<=>(a+b)^3-3ab(a+b+2)=-11`
Đặt `{(S=a+b),(P=ab):}`
Khi đó ta có `S^3-3P(S+2)=-11<=>(4(S^3+11))/(3(S+2))=4P`
Lại có `S^2>=4P` nên `S^2>=(4(S^3+11))/(3(S+2))`
`<=>(S^3-6S^2+44)/(3(S+2))<=0(S\ne-2)`
- TH1: `{(S^3-6S^2+44<=0),(3(S+2)>0):}<=>{(S<=-2,30213805),(S> -2):}<=>-2<S<-2,30213805(` Vô lý `)`
- TH1: `{(S^3-6S^2+44<=0),(3(S+2)>0):}<=>{(S<=-2,30213805),(S> -2):}<=>-2<S<-2,30213805(` Vô lý `)`
- TH1: `{(S^3-6S^2+44<=0),(3(S+2)>0):}<=>{(S<=-2,30213805),(S> -2):}<=>-2<S<-2,30213805(` Vô lý `)`
- TH1: `{(S^3-6S^2+44<=0),(3(S+2)>0):}<=>{(S<=-2,30213805),(S> -2):}<=>-2<S<-2,30213805(` Vô lý `)`
- TH2: `{(S^3-6S^2+44>=0),(3(S+2)<0):}<=>{(S>=-2,30213805),(S< -2):}<=>-2,30213805<S<-2`
mà `-7/3=-2,33333...<-2,30213805` nên `-7/3<S<-2(đfcm)`